PENGARUH PEMBIAYAAN KUR TERHADAP PERKEMBANGAN USAHA MIKRO DAN KECIL (UMK) NASABAH PT. BANK RIAU KEPRI SYARIAH KEDAI AIRTIRIS - M. Habib Alfarishi; M. Syahrullah; Muhammad Lisman (EL-EMIR Institute, 2025)
This study aims to analyze the influence of Kredit Usaha Rakyat (KUR) financing on the development of micro and small enterprises (MSEs) among the customers of PT. Bank Riau Kepri Syariah Kedai Air Tiris. The research employs a quantitative method with an associative approach. The population consists of all KUR financing recipients at PT. Bank Riau Kepri Syariah Kedai Air Tiris, with a sample of 100 respondents selected using probability sampling through a random sampling method. Data were collected using questionnaires and analyzed through simple linear regression with the assistance of IBM SPSS 27 software. The findings reveal that KUR financing has a positive and significant effect on the development of micro and small enterprises. This is evidenced by a significance value of 0.000 < 0.05. The coefficient of determination (R²) value of 0.412 indicates that 41.2% of the variation in micro and small enterprise development can be explained by KUR financing, while the remaining 58.8% is influenced by other factors beyond this study. These results confirm that KUR financing plays an important role in supporting the growth of micro and small enterprises, particularly in enhancing access to capital, production capacity, and market expansion. Therefore, optimizing the distribution of KUR financing is expected to strengthen the MSE sector as a key pillar of regional economic development.